Kindertagesstätten: öffentlicher Kommunikationsraum der Religionen. Ein Beitrag zur Diskussion einer „öffentlichen Religionspädagogik” - Edelbrock, Anke (Theo-Web, 2016)
Exemplified by child day care centers funded by local authority, the article underlines that academic religious pedagogy is responsible for religious and interreligious education in the public realm of a pluralist society. At the same time it is a contribution to the discussion about "Public Religious Pedagogy". To this end, structural and intellectual references are made to the concept of "Public Theology", in order to reflect on questions that arise in the area of elementary religious education. (English)